Pengaruh Motivasi Kerja Terhadap Kepuasan Kerja Pegawai pada Dinas Pemberdayaan Perempuan, Perlindungan Anak, Pengendalian Penduduk dan Keluarga Berencana (DP3AP2KB) Kecamatan Wawo - Nuranisa Nuranisa; Jaenab Jaenab; Mawar Hidayanti (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research aims to determine the significant influence of work motivation on employee job satisfaction at the women's empowerment, child protection, population control and family planning (DP3AP2KB) office in Wawo sub-district. This research is included in the category of associative population research. This research uses all employees at the women's empowerment, child protection, population control and family planning (DP3AP2KB) office in Wawo sub-district, totaling 55 employees. The research technique used is saturated samples. The instrument in this research is a questionnaire with a liter scale. Observation data collection techniques, questionnaires, literature study. The data analysis technique uses a validity test, a reliability test and then processed using SPSS. The results of the research show that work motivation has a significant effect on employee job satisfaction at the women's empowerment, child protection, population control and family planning (DP3AP2KB) office in Wawo sub-district.